Combustion characteristics of high ash Indian coal, wheat straw, wheat husk and their blends - Pritam Kumar (KeAi Communications Co., Ltd., 2021)
This work presents the combustion studies of high ash coal, wheat straw (WS), wheat husk (WH) and their blends to enhance the combustion performance of high ash coal. Coal, WS and WH were characterized by proximate analysis, ultimate analysis and gross calorific value (GCV) determination. Combustion performance of individual fuel and their blends were assessed by thermogravimetric (TGA) investigation followed by the study of various burning profile parameters such as ignition temperature (Ti), peak temperature (TP), burnout temperature (Tb), ignition index (IIX), combustion characteristics index (CIX) and burnout index (BIX). Experimental results show that coal has poor combustion characteristics compared to WS and WH. After the addition of 20% WS with coal Ti reduces from 383 °C to 257 °C, TP reduces from 452 °C to 287 °C, Tb reduces from 509 °C to 507 °C. Combustion performance indices analysis inferred that after the addition of 20% WH with coal, IIX improved from 2.81 to 5.14 mass2/min2 OC3 and CIX improved from 3.58 to 8.11 mass/min2 °C3. Activation energy (AE) analysis shows that coal having higher AE (82.13 kJ/mol) compared to WS (57.97 kJ/mol) and WH (56.56 kJ/mol). Based on ΔH, ΔG and ΔS analysis it was observed that individual combustion of coal is difficult compared to WS and WH combustion, whereas blending of WS/WH makes the combustion process significantly favorable.